2018
DOI: 10.1186/s40463-018-0255-1
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of human papillomavirus in pediatric tonsils: A systematic review of the literature

Abstract: Background: HPV-related head and neck cancer rates have been increasing in recent years, with the tonsils being the most commonly affected site. However, the current rate of HPV infection in the pediatric population remains poorly defined. The objective of this study was to systematically review and evaluate the prevalence and distribution of HPV in the tonsils of pediatric patients undergoing routine tonsillectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 30 publications
1
13
0
1
Order By: Relevance
“…Our finding that all tonsils were HPV negative fits in well with other reports, as absence or low numbers of HPV‐positive cases in benign tonsillar disease have been demonstrated previously . The largest study on benign tonsillar tissue evaluated 3377 benign tonsils without detecting any HPV .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our finding that all tonsils were HPV negative fits in well with other reports, as absence or low numbers of HPV‐positive cases in benign tonsillar disease have been demonstrated previously . The largest study on benign tonsillar tissue evaluated 3377 benign tonsils without detecting any HPV .…”
Section: Discussionsupporting
confidence: 88%
“…Our finding that all tonsils were HPV negative fits in well with other reports, as absence or low numbers of HPV-positive cases in benign tonsillar disease have been demonstrated previously. 26,28,[38][39][40][41][42] The largest study on benign tonsillar tissue evaluated 3377 benign tonsils without detecting any HPV. 43 These data are somewhat conflicting since a Belgian study found HPV detection rates in 12.5% (high-risk HPV) and 15% (low-risk HPV) in benign tonsillar tissue from adults and children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the information is scarce and controversial in children. Some reports show that HPV is present in palatine tonsils in 0-21% of children, without currently demonstrating its association with childhood cancer 13,14 . Malignant neoplasms of the palatine tonsil can manifest clinically by TA, dysphagia, otalgia, and verrucous lesions 15 .…”
Section: Discussionmentioning
confidence: 99%
“…), имеется бимодальный пик заболеваемости папилломами у детей раннего возраста и пожилых людей [1]. Основными путями инфицирования у детей является вертикальная передача от матери плоду и новорожденному, при тесном контакте, как правило, при поцелуях и сексуальных контактах [2].…”
Section: обоснованиеunclassified